Penelitian pada Kebutuhan Bank Susu Patuh Syariah Kepada Bayi Prematur di Malaysia: Research on the Need for Sharia-compliant Milk Banks for Premature Babies in Malaysia - Daud, Normadiah; Noordin, Nadhirah; Yusof, Zurita Mohd; Ashar, Nur Hidayah; Kusumawardhani, Paramitha Amelia (Jurnal Kebidanan Midwiferia, 2019)
The writing of this article aims to discuss the need for sharia compliant milk banks for premature babies. This study uses a qualitative approach using content analysis methods that focus on the textbooks, books, journals, articles and reports. The results of the discussion found that mother's milk contained many of the benefits needed by premature babies. When compared with formula milk, the nutritional content of breast milk is much better. There are several reasons why breastfeeding is now the main requirement in Malaysia, one of them is for premature babies.With this, the government seeks to meet ASI's needs by establishing a shariah compliant milk bank for mothers with breastfeeding problems. The results of the discussion found that Islam not only acknowledged the efficacy of ASI, it also emphasized the problem of maternal and adolescent mahram relationships. Therefore, the established milk bank must be in accordance with the guidelines set by the jurisprudence and the schools of Imam Shafi'i. In addition to needs, milk banks also provide benefits for Muslims by seeing an increase in premature baby birth statistics in Malaysia. It is in this condition of the emergency phase that a compliant sharia milk bank needs to be established. The milk bank that will be established can avoid the occurrence of problems overlapping the mahram according to the principle of Maqasid al-Shari'ah in the maintenance of implantable mahram purity.